The Swedish Heart Failure Registry: a living, ongoing quality assurance and research in heart failure. (2nd January 2019) - Savarese, Gianluigi; Vasko, Peter; Jonsson, Åsa; Edner, Magnus; Dahlström, Ulf; Lund, Lars H.
Abstract: Heart failure (HF) represents a global pandemic. Although in HF with reduced ejection fraction (HFrEF) randomized controlled trials have provided effective treatments, prognosis still remains poor, with signals of undertreatment. HF with mid-range EF (HFmrEF) has no evidence-based therapy, and its characterization is ongoing. Trials in HF with preserved EF (HFpEF) have failed to provide any effective treatment, but there are several concerns about their design. Thus, current challenges in the HF field are: 1) optimizing the use of existing treatments in HFrEF; 2) developing and proving efficacy of new treatments, and of new use of existing treatments in HFpEF and HFmrEF. Here we describe how registry-based research can improve knowledge addressing the unmet needs in HF, and in particular we focus on the contribution of the Swedish Heart Failure Registry to this field.